Guía de cuidados para enfermedad pulmonar obstructiva crónica en el adulto mayor, una revisión sistémica de la bibliografía - Sillo Andrango, Deysi Liliana (2024)
Chronic obstructive pulmonary disease (COPD) is a relevant condition globally in the field of medicine, as it causes disability in patients, disrupts family dynamics, and involves high healthcare costs. For this reason, this article aimed to develop a care guide for COPD in the elderly based on a systematic review of the literature. A systematic literature review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, transparently documenting the justification for the review and its findings. Various research works on Chronic obstructive pulmonary disease (COPD) care in the elderly were studied, highlighting the importance of several key components. Education focused on self-care and disease management, promotion of physical activity adapted to individual capabilities, adequate nutrition to combat malnutrition, and strengthening treatment adherence through continuous interventions and psychosocial support. In conclusion, a care guide for Chronic obstructive pulmonary disease in the elderly was developed based on the information gathered from the literature analysis of the reviewed articles.